TransTCR: Integrating TCRs and Transcriptomes Through Optimal Transport for Antigen Specificity Prediction - Wenbing Li; Yuansong Zeng; Ruipeng Huang; Yuanze Chen; Jinyun Niu; Ningyuan Shangguan; Siyuan He; Yuedong Yang (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Multi-compartmental Ni-MOF@C microcapsules for enhanced electrochemical detection of paracetamol and levofloxacin - Ruipeng Hao; Wanyu Xie; Danping Tian; Yifan Wang; Pei Zhang; Zheng Zhao; Xuwen Gao; Chen-zhong Li; Wenbo Lu (Analytica Chimica Acta, 2026)

Optimization of combined active morphing and passive flexibility for a heaving plate in freestream - Shunhang Chen; Hao Chen; Ruipeng Li; Dixia Fan; Zhenbo Lu (Ocean Engineering, 2026)

EGCG–selenocysteine nanoparticles inducing ferroptosis and apoptosis in tumor cells - Ziqi Cao; Wendong Qi; Yue Li; Xin Cong; Dejian Huang; Song Zhu; Shangwei Chen; Ruipeng Yu (Food Bioscience, 2026)

Neuroprotective effects and transport characteristics of selenium-enriched protein digestion products with different selenium species - Yue Zhang; Wendong Qi; Yue Li; Song Zhu; Xin Cong; Dejian Huang; Ruipeng Yu; Shangwei Chen (Food Bioscience, 2026)

Engineering human organoids for biomedical applications: materials, technologies, and translational potential - Yifei Gao; Zhu Yang; Lin Zhu; Changyu Long; Qiaofeng Li; Xuexia Jia; Ruipeng Chen; Zongwei Cai (Chemical Engineering Journal, 2026)

Magnetic field modulation of ferrimagnetic domain ordering for ultrasensitive xylene detection: a mechanistic investigation - Xiaoxue Xu; Jing Cao; Shuangming Wang; Yao Wang; ZhiXu Ye; RuiPeng Song; Zhuoyue Chen (Chemical Engineering Journal, 2026)

Process and mechanism of PPCPs degradation via high-temperature regulated FeCN composite catalyst-activated peroxymonosulfate - Faxiang Wu; Xiaotong Che; Xinyu Xu; Ruipeng Mao; Lei Chen (Journal of Water Process Engineering, 2025)

Function and mechanism of monosodium glutamate residue on improving the humification of chicken manure and spent mushroom substrates co-composting - Xing Wang; Zhiqing Duan; Xuejiao Yin; Zhengrong Hu; Jun Chen; Hui Li; Ruipeng Li; Ziru Li; Weiming Sun; Haihua Zhang; Tongao Yang; Yingchao Zhang; et al. (Journal of Environmental Chemical Engineering, 2025)

Applications of biosensing in assessing food flavor: advancements, challenges, and prospects - Kunli Xu; Yangfan Guo; Yadong Wang; Zhijie Yang; Haoying Han; Fanyu Meng; Yanbo Wang; Ruipeng Chen; Bei Wang (Food Chemistry, 2025)

Protective effect of selenium-enriched protein from Cardamine violifolia digestion products on PC12 cells injury induced by Aβ1-42 - Wendong Qi; Yue Zhang; Xin Cong; Dejian Huang; Ruipeng Yu; Shangwei Chen; Song Zhu (Food Bioscience, 2025)

Electrochemical detection of As(Ⅲ): Innovations with FeSx@MOF-808/Ti3C2Tx composite materials - Ruipeng Chen; Xuexia Jia; Xingpeng Huang; Zefeng Mao; Hong Zhang; Huanying Zhou; Shuyue Ren; Zhixian Gao (Chemical Engineering Journal, 2025)

Pollen-inspired novel silver/silica composite microsphere capable of synergistic bacteria-killing for bacteria-infected wound treatment - Hong Zhang; Guanyu Wang; Kang Qin; Ruipeng Chen; Wei Pang; Xuekun Bai; Ziming Li; Wengeng Guo; Bin Zheng; Huanying Zhou; Zhixian Gao (Chemical Engineering Journal, 2025)

Fe3O4@Au magnetic SERS nanotags-based vertical flow immunoassay for simultaneous detection of fumonisin B1, aflatoxin B1 and deoxnivalenol - Ruipeng Chen; Jianfeng Wu; Hui Wang; Muhammad Shemyal Nisar; Yongqi Li; Yuxuan Chen; Yu Mao; Xuemei Nan; Fan Zhang; Liang Yang; Xiangfang Tang; Jianwei Xie; et al. (Analytica Chimica Acta, 2025)

Digestive characteristics of Se-enriched proteins with different Se species and its effects on gut microbiota during in vitro APP/PS1 mice colonic fermentation - Yue Zhang; Wendong Qi; Xin Cong; Dejian Huang; Ruipeng Yu; Shangwei Chen; Song Zhu (Food Research International, 2025)

Effect of co-fermentation of Rhodotorula mucilaginosa with Saccharomyces cerevisiae on the quality and flavor profile of cider - Shijiao Liu; Ruipeng Wang; Yunong Zhang; Yiwei Dai; Sufang Zhang; Xinping Lin; Chaofan Ji; Huipeng Liang; Yingxi Chen (Food Bioscience, 2025)

Giant piezoelectricity in fluoropolymer fiber mats achieved by corona poling in water - Guanchun Rui; Zhenxing Chen; Elshad Allahyarov; Honghu Zhang; Ruipeng Li; Philip L. Taylor; Lei Zhu (Chemical Engineering Journal, 2024)

Chalcogen effect on the photovoltaic performance of nonfused-ring small molecular electron acceptors for efficient organic solar cells - Siyang Liu; Xiaowei Chen; Yinfeng Li; Xiaopeng Xu; Liyang Yu; Yuwei Duan; Ruipeng Li; Qiang Peng (Chemical Engineering Journal, 2024)

Programmable DNA tweezers-SDA for ultra-sensitive signal amplification fluorescence sensing strategy - Yingao Yang; Zixuan Zhou; Yifen Guo; Ruipeng Chen; Daoming Tian; Shuyue Ren; Huanying Zhou; Zhixian Gao (Analytica Chimica Acta, 2024)

Dietary supplementation of VA enhances growth, feed utilization, glucose and lipid metabolism, appetite, and antioxidant capacity of Chinese perch (Siniperca chuatsi) - Junliang Chen; Ming Zeng; Xu-Fang Liang; Di Peng; Ruipeng Xie; Dongliang Wu (Fish Physiology and Biochemistry, 2024)

Dietary soybean lecithin promoted growth performance and feeding in juvenile Chinese perch (Siniperca chuatsi) could be by optimizing glucolipid metabolism - Dongliang Wu; Di Peng; Xu-Fang Liang; Ruipeng Xie; Ming Zeng; Junliang Chen; Jie Lan; Ru Yang; Jiacheng Hu; Peisong Lu (Fish Physiology and Biochemistry, 2023)

Recent advances and prospects in wearable plant sensors - Ruipeng Chen; Shuyue Ren; Shuang Li; Dianpeng Han; Kang Qin; Xuexia Jia; Huanying Zhou; Zhixian Gao (Reviews in Environmental Science and Bio/Technology, 2023)

Bio-barcode assay: A useful technology for ultrasensitive and logic-controlled specific detection in food safety: A review - Yue Hou; Ruipeng Chen; Zhiguang Wang; Ran Lu; Yonghui Wang; Shuyue Ren; Shuang Li; Yu Wang; Tie Han; Shiping Yang; Huanying Zhou; Zhixian Gao (Analytica Chimica Acta, 2023)

Marine mammal morphometrics: 3D modeling and estimation validation - Changqun Zhang; Haojie Zhou; Fredrik Christiansen; Yujiang Hao; Kexiong Wang; Zhangbing Kou; Ruipeng Chen; Jie Min; Randall Davis; Ding Wang (Frontiers in Marine Science, 2023)
Techniques of 3D modeling have earned increasing popularity in scientific studies as they offered unprecedented traits in representing objects. As with all mathematical models, the 3D model will be useful once its accuracy has been validated with direct measurements and the robustness of its predictive capability tested. Although measures of body mass and volume are essential to comprehend the life history of animals, such morphometrics, especially total volume, are challenging to obtain from marine mammals due to their elusive nature, aquatic lifestyle, and large size. In this study, accurate measurements of body volume were directly detected from fresh carcasses of eleven finless porpoises ( Neophocaena asiaeorientalis sunameri ) and used to validate 3D models recreated from the same animals using Blender 3D graphics. Published models using truncated cones or elliptical shapes, based on 3, 5, 8, or 19 measurements of girths or heights & widths along the body, were also applied to porpoises to verify their accuracy. The Blender-generated 3D model produced the most accurate estimates of body volume compared to conventional truncated models, with a mean error of only 2.5% to the direct volume measurements. When photogrammetric images are available, the model can predict the body volumes based on total length alone. Similar accuracy was possible with the elliptical model using 19 height & width measurements (5% increments in total length). However, significant ( p < 0.001) inaccuracy resulted from truncated models with 3, 5, or 8 girth measurements and elliptical models with 3 or 5 height & width measurements, and the accuracy of these models also decreased significantly as the number of measurement sites was reduced. Moreover, Blender 3D models can be extrapolated to animals with images absent, and such predicted volumes were tested to be trustworthy (overall skill = 0.998, r = 0.998, p < 0.01). Therefore, we recommend that researchers use either digital 3D models or elliptical models with 5% increments sectioning the torso to obtain accurate estimates of the body volumes of free-ranging marine mammals.

Stimulus-responsive hydrogels: A potent tool for biosensing in food safety - Xiaoxiao Lin; Zhiguang Wang; Xuexia Jia; Ruipeng Chen; Yingkai Qin; Yalan Bian; Wei Sheng; Shuang Li; Zhixian Gao (Trends in Food Science & Technology, 2023)

Improving the performance of PM6 donor polymer by random ternary copolymerization of BDD and DTBT segments - Xiaowei Chen; Chentong Liao; Min Deng; Xiaopeng Xu; Liyang Yu; Ruipeng Li; Qiang Peng (Chemical Engineering Journal, 2023)

A Manta Ray Robot with Soft Material Based Flapping Wing - Qimeng Liu; Hao Chen; Zhenhua Wang; Qu He; Linke Chen; Weikun Li; Ruipeng Li; Weicheng Cui (Journal of Marine Science and Engineering, 2022)
Recent research on robotic fish mainly focused on the bionic structure design and realizing the movement with smart materials. Although many robotic fish have been proposed, most of these works were oriented toward shallow water environments and are mostly built with purely rigid structures, limiting the mobility and practical usability of robotic fish. Inspired by the stability of the real manta ray, a manta ray robot design is proposed with soft material made flapping wing based on an open-source ROV (Remotely Operated Vehicle). The flapping wing structure with three different materials mimics the wide pectoral fins of real manta rays, which have bones, muscles, and skin. Furthermore, its modular design makes it easy to install and disassemble. The kinematic and hydrodynamic analysis of the manta ray robot are simulated in this paper. The actual manta ray robot is fabricated and several sets of test are performed in the pool. The robot can swim forward continually and stably with a simple rolling and pitching pattern.

Evaluation of the Biodiversity Conservation Function in Liaohe Delta Wetland, Northeastern China - Wenying Yu; Ruipeng Ji; Xiuzhen Han; Long Chen; Rui Feng; Jinwen Wu; Yushu Zhang (Journal of Meteorological Research, 2020)

Modeling Canopy Carbon and Water Fluxes Using a Multilayered Model over a Temperate Meadow in Inner Mongolia - Nina Chen; Anzhi Wang; Juan An; Yushu Zhang; Ruipeng Ji; Qingyu Jia; Ziqi Zhao; Dexin Guan (International Journal of Plant Production, 2020)
To incorporate canopy vertical structure in a process-based model over a temperate meadow, a multilayered model estimated canopy carbon flux ( F c ) and water flux ( LE ) was applied by comparing with eddy covariance measurements in Inner Mongolia, China. Simulations of diurnal, seasonal CO 2 and H 2 O fluxes and model sensitivity to parameters and variables were analyzed. The results showed that the model underestimated F c and LE by about 0.6% and 5.0%, respectively. It was able to simulate the diurnal and seasonal variation of F c and LE and performed well during the day and in the growing season, but poorly at night and early in the growing season. F c was more sensitive to the leaf nitrogen content distribution coefficient and maximum catalytic activity of Rubisco, whereas LE showed greater sensitivity to the stomatal conductance parameter a 1 , empirical coefficient of stomatal response to saturated vapor pressure difference V pds0 , and minimum stomatal conductance of CO 2 g sc0 . The response of F c to environmental factors was ranked as air CO 2 concentration ( C a ) > air temperature ( T a ) > photosynthetically active radiation (PAR) > soil water content ( θ sm ) > vapor pressure deficit (VPD) > wind speed ( u 0 ). The response of LE to environmental factors was ranked as T a > VPD > θ sm > PAR> C a > u 0 . The response of LE to vegetation characteristic parameters was greater than that of F c .

Molecular characterization of putative biocorroding microbiota with a novel niche detection of Epsilon ‐ and Zetaproteobacteria in Pacific Ocean coastal seawaters - Hongyue Dang; Ruipeng Chen; Lin Wang; Sudong Shao; Lingqing Dai; Ying Ye; Lizhong Guo; Guiqiao Huang; Martin G. Klotz (Environmental Microbiology, 2011)
Summary Submerged metal surfaces in marine waters undergo rapid microbial colonization and biocorrosion, causing huge damage to marine engineering facilities and significant financial losses. In coastal areas, an accelerated and particularly severe form of biocorrosion termed accelerated low water corrosion (ALWC) is widespread globally. While identification of biocorroding microorganisms and the dynamics of their community structures is the key for understanding the processes and mechanisms leading to ALWC, neither one is presently understood. In this study, analysis of constructed clone libraries and qPCR assays targeting group‐specific 16S rRNA or functional marker genes were used to determine the identity and abundance of putative early carbon steel surface‐colonizing and biocorroding microbes in coastal seawater. Diverse microbial groups including 10 bacterial phyla, archaea and algae were found to putatively participate in the surface‐colonizing process. Analysis of the community structure of carbon steel surface microbiota revealed a temporal succession leading to ALWC. By extending the current state of knowledge, our work demonstrates the global importance of Alphaproteobacteria (mainly Rhodobacterales ), Gammaproteobacteria (mainly Alteromonadales and Oceanospirillales ), Bacteroidetes (mainly Flavobacteriales ) and microalgae as the pioneer and sustaining surface colonizers that contribute to initial formation and development of surface biofilms. We also discovered Epsilonproteobacteria and the recently described Zetaproteobacteria as putative corrosion‐causing microorganisms during early steps of the ALWC process. Hence, our study reports that Zetaproteobacteria may be ubiquitous also in non‐hydrothermal coastal seawaters and that ALWC of submerged carbon steel surfaces in coastal waters may involve a highly diverse, complex and dynamic microbial consortium. Our finding that Epsilon ‐ and Zetaproteobacteria may play pivotal roles in ALWC provides a new starting point for future investigation of the ALWC process and mechanism in marine environments. Further studies of Epsilon ‐ and Zetaproteobacteria in particular may thus help with the design of effective corrosion prevention and control strategies.

Gene cloning, expression and characterization of a cold-adapted lipase from a psychrophilic deep-sea bacterium Psychrobacter sp. C18 - Ruipeng Chen; Lizhong Guo; Hongyue Dang (World Journal of Microbiology and Biotechnology, 2011)